Implementasi Pendidikan Kewirausahaan Dalam Membangun Jiwa Wirausaha Di SMK Negeri 3 Palangka Raya - Bella Isa Putri; Eni Eni; Sela. M; Igo Aditia Putra; Defri Triadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to examine the implementation of entrepreneurship education in building an entrepreneurial spirit at SMK Negeri 3 Palangka Raya. The research method used is a qualitative descriptive method with data collection techniques through interviews, observations, and documentation studies. The results of the study show that entrepreneurship education at SMK Negeri 3 Palangka Raya has been implemented through various programs and activities that support the development of students' entrepreneurial skills and mentality. The program includes entrepreneurship training, student business projects, and cooperation with various external parties such as the industrial world and local businesses. Obstacles faced in implementation include limited resources, lack of support from parents, and lack of awareness among students about the importance of entrepreneurship. Nevertheless, efforts to improve the quality of entrepreneurship education continue to be carried out through increasing teacher capacity, curriculum development, and improving supporting facilities. This study concludes that entrepreneurship education plays an important role in shaping the entrepreneurial spirit among students, but requires more comprehensive support from various parties to achieve optimal results.